Antioxidant Activities and Identification of an Active Compound from Rambutan (Nephelium lappaceum L.) Peel - Mistriyani Mistriyani; Sugeng Riyanto; Anjar Windarsih; Abdul Rohman (Universitas Gadjah Mada, 2021)
The consumption of rambutan fruit resulted in a vast amount of peels and seeds waste. Therefore, the exploration of active compounds having beneficial effects on human health, such as antioxidants, is very lucrative. This research was aimed to isolate and to identify the active compound as an antioxidant from rambutan peel. The powdered rambutan peel was extracted with a maceration technique using methanol then fractionated using petroleum ether, chloroform, and ethyl acetate to get the corresponding fractions. The extract and fractions were determined for its antioxidant activities in vitro using 2,2’-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging and metal-chelating assay. The ethyl acetate fraction exhibited the highest antiradical activity with an IC50 value of 26.22 μg/mL and metal-chelating activity, accounting for 12.32%. The antioxidant activities of extract and fractions correlated with its phenolics and flavonoid contents. Identification of active compounds using FTIR, GC-MS, and NMR resulted in the chemical formula of C7H6O4, identified as 3,4-dihydroxybenzoic acid.